PROTEIN PHOSPHATASE 2A-B′γ Controls Botrytis cinerea Resistance and Developmental Leaf Senescence . Issue 2 (28th October 2019) - Durian, Guido; Jeschke, Verena; Rahikainen, Moona; Vuorinen, Katariina; Gollan, Peter J.; Brosché, Mikael; Salojärvi, Jarkko; Glawischnig, Erich; Winter, Zsófia; Li, Shengchun; Noctor, Graham; Aro, Eva-Mari; et al.
Abstract : PP2A-B′γ interacts with CALCIUM-DEPENDENT PROTEIN KINASE1 and age-dependently controls salicylic acid-related signaling in plant immunity and developmental leaf senescence. Abstract: Plants optimize their growth and survival through highly integrated regulatory networks that coordinate defensive measures and developmental transitions in response to environmental cues. Protein phosphatase 2A (PP2A) is a key signaling component that controls stress reactions and growth at different stages of plant development, and the PP2A regulatory subunit PP2A‐B′γ is required for negative regulation of pathogenesis responses and for maintenance of cell homeostasis in short-day conditions. Here, we report molecular mechanisms by which PP2A‐B′γ regulates Botrytis cinerea resistance and leaf senescence in Arabidopsis ( Arabidopsis thaliana ). We extend the molecular functionality of PP2A‐B′γ to a protein kinase–phosphatase interaction with the defense-associated calcium-dependent protein kinase CPK1 and present indications this interaction may function to control CPK1 activity. In presenescent leaf tissues, PP2A-B′γ is also required to negatively control the expression of salicylic acid-related defense genes, which have recently proven vital in plant resistance to necrotrophic fungal pathogens. In addition, we find the premature leaf yellowing of pp2a - b′γ depends on salicylic acid biosynthesis via SALICYLIC ACID INDUCTION DEFICIENT2 and bears the hallmarks of developmental leaf senescence. We propose PP2A-B′γ age-dependently controls salicylic acid-related signaling in plant immunity and developmental leaf senescence.